Perancangan Coworking Space Di Pekanbaru Berdasarkan Prinsip Desain Ludwig Mies Van Der Rohe - Noni Septiani; Pedia Aldy; Yohannes Firzal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Coworking Space is a place where start-ups work along side each other in flexible environtment, which desks are available to rent on daily, weekly, monthly, and yearly basis. The space is in thesame line with Ludwig Mies van der Rohe design principle in function efficiency and simplicity of form. Through the design principle, concept of this coworking space design is Share Through The Glass, which is defined as interaction between outer and inner of building with glass wall. This is based on coworking space characters, such as collaboration, community, sustainability, openness, and accessibility. The concept is applied on zoning, mass order, massing, and facade. Zoning, mass order, and massing are based on Ludwig Mies van der Rohe design principle in simple geometric pattern. By applying vertical and horizontal surface composition principle, colomn and beam become building facade.Keywords: Start-up, Coworking Space, Ludwig Mies van der Rohe